Kanclerski model sprawowania władzy wykonawczej w Republice Federalnej Niemiec a resortowy system egzekutywy w Republice Austrii - Dudek, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article compares the model of executive power in the Federal Republic of Germany and the Republic of Austria. The chancellor system is a variant of the cabinet system and was first introduced in the German Basic Law on May 23, 1949. In contrast, the ministerial system, also a variation of the cabinet model of the executive, is now rarely found - some of its characteristics can still be observed in the Czech Republic. This model was particularly popular in the 1920s in European states that adopted a parliamentary system of government. In both systems, the head of state is the president, but the method of their election differs in each case. The head of government in both countries is the chancellor, but their position and scope of competencies vary.
Keywords: Republika Federalna Niemiec; Republika Austrii; system kanclerski; system resortowy; władza wykonawcza; Federal Republic of Germany; Republic of Austria; chancellor system; ministerial system; executive power